Effect of non-genetic factors and estimation of heritability of lifetime traits in Sahiwal cattle - P. Kathiravan; G.K Sachdeva; R.S. Gandhi; P. K. Singh; T.V. Raja; K.N. Raja; S. Rajesh Kumar (Journal of Livestock Biodiversity, 2025)
The present study aimed to evaluate the influence of non-genetic factors and to estimate heritability of lifetime traits in Sahiwal cattle. Lifetime lactation records of 901 Sahiwal cows spread over a period of 33 years from 1973 to 2005, maintained at National Dairy Research Institute, Karnal and Government Livestock Farm, Chakganjaria, Lucknow were utilized. The mean total milk yield was significantly higher (P < 0.01) in Karnal herd compared to that of Lucknow herd in the first five lactations. The effect of season of calving had significant influence on total milk yield in second and fourth lactations of Sahiwal cattle. The effect of different periods of calving was significant (P<0.01) on the total milk yields of first and third lactations, whereas no significant effect of period was observed on total milk yields of second, fourth and fifth lactations. Among the interaction effects, the effect of herd X season interaction had significant influence on second and fifth lactation total milk yields, whereas the effect of herd X period interaction was significant on first and second lactation total milk yields. The overall mean lifetime milk yield in Sahiwal cattle was 6430.37±72.57 kg with an average of Karnal and Lucknow herd being 7693.23 ±106.45 and 5879.47±67.84 kg respectively. The mean longevity was found to be significantly higher in Lucknow herd (3452.85±70.83 days) as compared to that of Karnal herd (2959.13±96.28 days). The effect of season of birth was not significant on longevity with a range of 3128.02±135.14 days (autumn) to 3243.55±99.63 days (rainy season). However, the period of birth was found to have significant effect on longevity. The heritability estimates of longevity and lifetime milk yield were found to be 0.276±0.096 and 0.042±0.066 respectively.